Mutation analysis and copy number alterations of KIF23 in non-small-cell lung cancer exhibiting KIF23 over-expression - Vikberg, Ann-Louise (Onco Targets Ther, 2017)
KIF23 was recently suggested to be a potential molecular target for the treatment of lung cancer. This proposal is based on elevated expression of KIF23 in several tumors affecting breast, lung, brain, and liver, and also on the presence of KIF23 mutations in melanoma and colorectal cancer. Recently, we identified a mutation in the KIF23 gene causing a rare hereditary form of dyserythropoietic anemia (CDA III) with predisposition to blood cancer. We suggested that KIF23 overexpression in tumors might be due to the presence of activating somatic mutations, and therefore, mutation screening of the KIF23 in 15 non-small-cell lung cancer (NSCLC) cases with elevated expression level of KIF23 was undertaken. Eight sequence variants were found in all samples. Furthermore, one variant was present in two cases, and one variant was case specific. Nine variants were previously reported while one variant lacks frequency information. Nine of ten cases available for single nucleotide polymorphism-array analysis demonstrated aberrant karyotypes with additional copy of entire chromosome 15. Thus, no activating somatic mutations in coding regions of the KIF23 were found. Furthermore, no mutations were detected in cell cycle genes homology region in KIF23 promoter responsible for p53-dependent repression of KIF23 expression. We showed that the elevated level of KIF23 could be due to additional copy of chromosome 15 demonstrated in 90% of NSCLC cases analyzed in this study. Considering the crucial role of KIF23 in the final step of mitosis, the gene is a potential molecular marker, and for better understanding of its role in cancer development, more tumors should be analyzed.